EMPOWERING WOMEN THROUGH HOME INDUSTRY (PARTICIPATORY ACTION RESEARCH-BASED STUDY IN GAMPONG POST-CONFLICT COT LAMME - ACEH BESAR) - Rasyidah, Rasyidah; Dendi, Dwi; Sakdiah, Sakdiah; Maisarah, Siti; Fatimah, Fatimah; M Husein, Mustabsyirah; Rizkitullah, Harir (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The service targets female home industry (HI) actors from Gampong Cot Lamme Aceh Besar who are still having social and psychological impacts due to the conflict. They tend to be pessimistic and apathetic in managing their business, even though their business contributes to the family economy. An Action Research approach was used to ensure community involvement throughout the program. The research problem formulation is how to model empowering women's home industries based on action research, strengthen home industries, and encourage community involvement, especially HI actors. The service results show that the community empowerment model is implemented through six focuses: strengthening business mentality and spirit, improving product quality, improving business management skills, expanding marketing access, and building networks. Mental strengthening of business is carried out through a religious approach based on recitation. The result was that 14 businesses had official business licensing documents, packaged products, and had diversification of salted duck egg products. Marketing is carried out with the label